2022
DOI: 10.1186/s13059-022-02752-5
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal molecular signatures of inflammation, energy metabolism, and vesicle biology in human Huntington disease peripheral tissues

Abstract: Background A major challenge in neurodegenerative diseases concerns identifying biological disease signatures that track with disease progression or respond to an intervention. Several clinical trials in Huntington disease (HD), an inherited, progressive neurodegenerative disease, are currently ongoing. Therefore, we examine whether peripheral tissues can serve as a source of readily accessible biological signatures at the RNA and protein level in HD patients. Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 76 publications
0
19
0
1
Order By: Relevance
“…Moreover, the miHTT was also found in the CSF of the animal post-treatment, further confirming that EVs are indeed the source of miHTT-AAV propagation in the HD brain. 125 In a patient-based clinical trial, transcriptomics and proteomicsbased screening of peripheral EVs isolated from HD patients displayed a dysregulated EV profile, further suggesting that other than a predictor of pathogenic state, EVs can also be utilized as a biomarker for HD 126 (Table 1).…”
Section: Huntington's Diseasementioning
confidence: 99%
“…Moreover, the miHTT was also found in the CSF of the animal post-treatment, further confirming that EVs are indeed the source of miHTT-AAV propagation in the HD brain. 125 In a patient-based clinical trial, transcriptomics and proteomicsbased screening of peripheral EVs isolated from HD patients displayed a dysregulated EV profile, further suggesting that other than a predictor of pathogenic state, EVs can also be utilized as a biomarker for HD 126 (Table 1).…”
Section: Huntington's Diseasementioning
confidence: 99%
“…Philipp Nitzschner 1 Ronja Wagner 1 Julia Hummel 1 Franziska Hoschek 1 Maximilian Wagner 1 Alshaimaa Abdelmoez 1,2 Björn von Einem 1 G. Bernhard Landwehrmeyer 1 Sarah J. Tabrizi 3 Michael Orth 1,4,5…”
Section: Andreas Neuederunclassified
“…1 In line with this, we have recently shown that molecular signatures of inflammation, energy metabolism and vesicle biology are different in peripheral tissues of HTT mutation carriers (MTM-HD study). 2 EVs are secreted by most, if not all cells. They are composed of lipids, proteins, RNAs and other small molecules and are generally categorised into three subtypes: exosomes, ectosomes and apoptotic bodies.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations